1997
DOI: 10.1103/physrevb.55.15895
|View full text |Cite
|
Sign up to set email alerts
|

Local heteroepitaxy of diamond on silicon (100):mA study of the interface structure

Abstract: An extensive study of the interface between highly oriented chemical vapor deposition diamond films and silicon has been performed using atomic force microscopy ͑AFM͒, high-resolution scanning electron microscopy ͑HRSEM͒, x-ray photoelectron diffraction ͑XPD͒, and transmission electron diffraction. The initial roughness of the silicon substrate has been investigated by AFM. Hydrogen plasma has been found to produce pits on the biased substrate surface. The local order of the ␤-SiC grown on silicon ͑100͒ during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The ionic species react with the substrate, resulting in the formation of a silicon carbide layer with improved adhesion when silicon is used as the substrate [106]. Nucleation densities higher than 1×10 11 cm -2 have been obtained with this method [107], however, Maillard-Schaller et al reported surface damage induced on a silicon substrate during the BEN that happened in the form of holes that could be as deep as 2-3 µm and as large as 200-300 nm in diameter [108].…”
Section: Effect Of Substrate Pre-treatment On Diamond Nucleationmentioning
confidence: 99%
“…The ionic species react with the substrate, resulting in the formation of a silicon carbide layer with improved adhesion when silicon is used as the substrate [106]. Nucleation densities higher than 1×10 11 cm -2 have been obtained with this method [107], however, Maillard-Schaller et al reported surface damage induced on a silicon substrate during the BEN that happened in the form of holes that could be as deep as 2-3 µm and as large as 200-300 nm in diameter [108].…”
Section: Effect Of Substrate Pre-treatment On Diamond Nucleationmentioning
confidence: 99%
“…We are therefore reluctant to draw any conclusions on the presence of a specific SiC structure in the surface layer, although other investigations have shown that ␤-SiC is frequently formed on Si͑100͒ substrates. 9,11,20 The analysis of the C 1s and Si 2p core level also shows the evolution of a carbide interface and, for temperature below 900°C, the growth of the carbon overlayer as already described in the previous paragraph. In addition, the analysis of the XPS core-level spectra enables us now to separate the contributions from the carbide interface, the substrate, and the overlayer.…”
Section: Resultsmentioning
confidence: 56%
“…This method has also been used to fabricate diamond-based device structures, [20,21] and to deposit highly oriented diamond films using Ir/SrTiO 3 substrates, with promising results, [22] but this method may damage the substrate. Maillard-Schaller et al [23] reported surface damage on a silicon substrate in the form of holes that could be as deep as 2-3 mm and as large as 200-300 nm in diameter. After the nucleation step, the growth is followed by diamond deposition in a standard CVD reactor, under proper growth conditions (GC).…”
Section: Introductionmentioning
confidence: 99%